TAMAN NASIONAL KUTAI DAN PEREBUTAN SUMBERDAYA ALAM - Robert Siburian (LIPI Press, 2008)
National Park has big resources. They could be used for economic development in a certain region. But that expectation couldn’t be carried out. National park functions are not only for economic development but also for keeping environmental balance, which is more important. Both functions have made conflict of interests between some stakeholders. Some of them want to use these resources in order to exploit them and ignore deforestation impact, while others want to preserve the national park to maintain its good condition for the future. This conflict of interests has been more intense since governmental decentralization system was overthrown. In this paper, the author would like to explain this phenomenon, especially by using the case of Kutai National Park. This paper is a result of a research conducted in July, 2006.